Selecting a Project Delivery System for Wastewater Treatment Plants With Related-Indicators Under a Pythagorean Fuzzy Environment - Li, Huimin; Cao, Yongchao; Su, Limin; Wang, Fuqiang (Frontiers in Environmental Science, 2022)
Identifying an appropriate project delivery system for wastewater treatment plants (PDSWTPs) plays an important role for wastewater industry decision makers. The object of this study is to deal with PDSWTPs selection with related-indicators. The works of this study are as follows: (1) the case with related-indicators is innovatively considered as to specific water industry, and Bonferroni mean operator and Pythagorean fuzzy sets are introduced to PDSWTPs selection, which can handle complexity and fuzziness for the actual application. (2) Pythagorean fuzzy weighted Bonferroni mean (PFWBM) and Pythagorean fuzzy weighted geometry Bonferroni mean (PFWGBM) operators are used to aggregate all related-indicators in PDSWTPs selection, and taking full advantage of PFWBM and PFWGBM operators, a selection framework for PDSWTPs is constructed. (3) To show the robustness, the PDSWTPs selection results were given with different parameters in proposed operators. Finally, a practice example is appeared, and the results show the effective and applicable.